Comparing Welfare Regime Changes: Living Standards and the Unequal Life Chances of Different Birth Cohorts - Louis Chauvel (Intergenerational Justice Review)
This article focuses on inter-and intra-cohort inequalities of living standards in a comparative perspective, underlining the diversity of national responses to the challenges of economic slow down, stronger economic competition and globalisation and their implications on different age groups. The aim is to make a connection between national Welfare regimes and the emergence of specific cohort-based economic constraint patterns in different countries, which are about to produce specific social generations2. I highlight the emergence of ‘scarring effects’; that is the irreversible consequences of (short term) social fluctuations in the context of socialisation on the (long term) life chances of different birth cohorts. These scarring effects can affect specific birth cohorts in countries where the welfare regime provides the context for increasing polarisation between middle-aged insiders and young outsiders. This is characterised by a lack of resilience to early career difficulties faced by cohorts of young adults.